Assessment and Estimation of Trace Elements in Azadiracta indica from Mining Area by EDXRF Technique - Jyothsna, S.; Manjula, G.; Sammaiah, D. (New Insights into Physical Science Vol. 12, 2021)
The effect of mining activity on environment has one of the major concerns for public health. Generally mining releases heavy toxic elements such as As, Pb, Cd and Hg. These metals have potential to accumulate in different organs of the body for long period of time causes toxicity and unwanted effects on human health. The Present study deals with the trace elemental analysis of selected medicinal plant of Azadiracta indica from mining area by EDXRF technique. EDXRF is one of the most powerful, non-destructive, multi-elemental and high sensitive analytical method. The thirteen elements such as P, S, Cl, K, Ca, Mn, Fe, Cu, Zn, Se, Br, Rb and Sr were identified and their elemental concentrations were determined. The results were compared with control sample and NIST1515 apple leaves, it shows various elements found to present in different quantities in same plant from different areas. High elemental concentrations were found in Azadiracta indica from coal mining area, this may be due to of coal mining area has been associated with enhancement of heavy toxic elements absorbed by soil. The analysis of this study also gives the presence of elements in the environment pollution from mining area plant sample. Thus we have recommended that the people living in mining areas are to be very cautious in daily life processes due to the exposure of heavy metals and toxic chemical elements from coal mining area has harmful affect on human health.